Taking aim at the arms trade : NGOs, global civil society and the world military order - Stavrianakis, Anna (Zed Books ; Distributed in the USA exclusively by Palgrave Macmillan, 2010)
Taking Aim at the Arms Trade takes a critical look at the ways in which NGOs portray the arms trade as a problem of international politics and the strategies they use to effect change. Anna Stavrianakis exposes the tensions inherent in NGOs' engagement with the arms trade and argues for a re-examination of dominant assumptions about NGOs as global civil society actors.